Effect of Naoxintong Capsules on the Activities of CYP450 and Metabolism of Metoprolol Tartrate in Rats Evaluated by Probe Cocktail and Pharmacokinetic Methods. (23rd September 2019) - Ouyang, Huizi; Shen, Jiayuan; Huang, Xuhua; Ma, Wenjuan; Jia, Qi; Yao, Guangzhe; Tang, Zhidan; Zhang, Dandan; Sun, Mengjie; Teye Azietaku, John; Hao, Jia; Gao, Xiumei; et al.
Abstract : Naoxintong capsule (NXT), a prescribed Chinese medicine, has been used clinically for more than 20 years and is widely received by patients. We determined five probe drugs, namely, omeprazole (CYP2C19), midazolam (CYP3A4), phenacetin (CYP1A2), tolbutamide (CYP2C9), and dextromethorphan (CYP2D6) to study the potential influences of NXT on the activities of CYP enzymes and assessed the pharmacokinetics effect of NXT on metoprolol tartrate in rat plasma. The study showed that AUC(0–24) and AUC(0–∞) of midazolam (CYP3A4) in NXT coadministration group (283.7 ± 65.2 h·ng·mL −1 and 292.0 ± 75.1 h·ng·mL −1 in group B; 295.7 ± 62.7 h·ng·mL −1 and 299.5 ± 60.0 h·ng·mL −1 in group C) were significantly decreased as compared to another group (416.8 ± 82.3 h·ng·mL −1 and 424.9 ± 77.9 h·ng·mL −1 in group A), while that of dextromethorphan (CYP2D6) showed an opposite tendency (540.7 ± 119.7 h·ng·mL −1 and 595.3 ± 122.2 h·ng·mL −1 in group A, 760.6 ± 184.9 h·ng·mL −1 and 788.7 ± 211.0 h·ng·mL −1 in group B, and 734.3 ± 118.5 h·ng·mL −1 and 757.2 ± 105.4 h·ng·mL −1 in group C). Moreover, NXT preadministration can enhance the metabolism of metoprolol tartrate and reduce the metabolism of O-demethylmetoprolol. The results indicated that NXT had potential effects in inducing CYP3A4 and inhibiting CYP2D6 in the metabolism of metoprolol tartrate. It suggests that patients who coadministered NXT and metoprolol tartrate should be advised of potential herb-drug interactions (HDIs) to reduce therapeutic failure or accelerated toxicity of conventional drug treatment.